Diluted chemical bath deposition of CdZnS as prospective buffer layer in CIGS solar cell. Issue 8 (15th April 2021) - Munna, F.T.; Selvanathan, Vidhya; Sobayel, K.; Muhammad, Ghulam; Asim, Nilofar; Amin, Nowshad; Sopian, Kamaruzzaman; Akhtaruzzaman, Md.
Abstract: In this study, dilute chemical bath deposition technique has been used to deposit CdZnS thin films on soda-lime glass substrates. The structural, morphological, optoelectronic properties of as-grown films have been investigated as a function of different Zn 2+ precursor concentrations. The X-ray diffractogram of CdS thin-film reveals a peak corresponding to (002) plane with wurtzite structure, and the peak shift has been observed with the increase of the Zn 2+ concentration upon formation of CdZnS thin film. From morphological studies, it has been revealed that the diluted chemical bath deposition technique provides homogeneous distribution of film on the substrate even at a lower concentration of Zn 2+ . Optical characterization has shown that the transparency of the film is influenced by Zn 2+ concentration and when the Zn 2+ concentration is varied from 0 M to 0.0256 M, bandgap values of resulting films range from 2.42 eV to 3.90 eV while. Furthermore, electrical properties have shown that with increasing zinc concentration the resistivity of the film increases. Finally, numerical simulation validates and suggests that CdZnS buffer layer with composition of 0.0032 M Zn 2+ concentration would be a promising candidate in CIGS solar cell.